1991
DOI: 10.1128/jcm.29.7.1429-1435.1991
|View full text |Cite
|
Sign up to set email alerts
|

Immunoblot analysis of the humoral immune response to Leishmania donovani infantum polypeptides in human visceral leishmaniasis

Abstract: Using the immunoblot technique, we have compared the reactions of Leishmania donovani infantum polypeptides with the immunoglobulin G of human sera from patients with parasitologically proven L. d. infantum infection, with suspected visceral leishmaniasis, and with other leishmaniases, protozoiases, helminthiases, and fungal or bacterial diseases. A 94-kDa component reacted with all L. d. infantum-infected sera and with 75% of sera from patients with clinical and serological but no parasitological diagnoses. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…Although most of the bands were common to all sera we detected a certain variability in the antigen-binding pattern revealed by different samples, particularly in the 30-19 kD region. In agreement with previous reports for the humoral response to Leishmania donovani in human visceral leishmaniasis (Rolland-Burger et al 1991) we observed that the most intensively labelled bands corresponded to molecular masses of 94, 75, 70, 66-60, 40-30, 20-17. We also observed that the sera from these dogs strongly react with the Leishmania purified Hsp70 (70Kd), LiP0 (32kd), H2A (14kd), LiP2a and LiP2b (13kd) proteins (Laboratory data).…”
Section: Immunoblot Analysis Of the Reactivity Of Sera Ah And Csfsupporting
confidence: 93%
“…Although most of the bands were common to all sera we detected a certain variability in the antigen-binding pattern revealed by different samples, particularly in the 30-19 kD region. In agreement with previous reports for the humoral response to Leishmania donovani in human visceral leishmaniasis (Rolland-Burger et al 1991) we observed that the most intensively labelled bands corresponded to molecular masses of 94, 75, 70, 66-60, 40-30, 20-17. We also observed that the sera from these dogs strongly react with the Leishmania purified Hsp70 (70Kd), LiP0 (32kd), H2A (14kd), LiP2a and LiP2b (13kd) proteins (Laboratory data).…”
Section: Immunoblot Analysis Of the Reactivity Of Sera Ah And Csfsupporting
confidence: 93%
“…In a previous study (Rolland-Burger et al 1991), we reported that a 94-kDa component from L. infantum promastigotes was recognized in immunoblot by serum antibodies from VL-infected Greek patients, but not by sera from patients with other leishmaniases, protozoiases, helminthiases, and fungal or bacterial diseases. The present report confirms and extends these results.…”
Section: Discussionmentioning
confidence: 79%
“…Cross-reactions among various species of Leishmania are well known (McMahon-Pratt & David 1981, Lepay, Nogueira & Cohn 1983, Gardiner, Jaffe & Dwyer 1984, Anthony et al 1985, Colomer-Gould et al 1985, Edges et al 1985, Bouvier, Etges & Bordier 1987, allowing crossreactivities among VL and CL sera. In particular, we previously showed (Rolland-Burger et al 1991) that the 94 kDa antigen was detected by 1 : 200 diluted VL sera in L. infantum and L. donovani species, but also in those causing CL (L. tropica, L. major, L. guyanensis, L. mexicana). However, the 94 kDa antigen was not detected by 1 : 200 diluted CL sera.…”
Section: Infanrum Lem 497 Polypeptides Separated By 10% Polyacrylamentioning
confidence: 94%
See 2 more Smart Citations